Exploring Immune-Related Prognostic Signatures in the Tumor Microenvironment of Colon Cancer - Cao, Lichao; Li, Tong; Ba, Ying; Chen, Erfei; Yang, Jin; Zhang, Hezi (Frontiers in Genetics, 2022)
Background: Colon cancer is a common malignant tumor with poor prognosis. This study aimed to explore the immune-related prognostic signatures and the tumor immune microenvironment of colon cancer. Methods: The mRNA expression data of TCGA-COAD from UCSC Xena platform and the list of immune-related genes (IRGs) from ImmPort database were used to identify the immune-related differentially expressed genes (DEGs). Then, we constructed an immune-related risk score prognostic model and validated its predictive performance in the test dataset, the whole dataset, and two independent GEO datasets. In addition, we explored the differences of tumor-infiltrating immune cell types, tumor mutation burden (TMB), microsatellite status and expression levels of immune checkpoints and their ligands between the high-risk score group and low-risk group. Moreover, the potential value of the identified immune-related signature respect to immunotherapy was investigated based on an immunotherapeutic cohort (Imvigor210) treated by anti-PD-L1 agent. Results: 7 immune-related DEGs were identified as prognostic signatures. The areas under the curves (AUCs) of the constructed risk score model for overall survival (OS) were calculated (training dataset: 0.780 at 3 years, 0.801 at 4 years, and 0.766 at 5 years; test dataset: 0.642 at 3-years, 0.647 at 4-years, and 0.629 at 5-years; the whole dataset: 0.642 at 3-years, 0.647 at 4-years, and 0.629 at 5-years). In the high-risk score group of the whole dataset, patients had worse OS, and higher TMN stages, higher advanced pathological stage, and higher TP53 mutation rate (P <0.05). In addition, high level of NK cells resting or Macrophages M0, and high TMB were significantly related to poor OS (P<0.05). And we observed that high-risk score patients had high level expression of PD-L1, PD-1 and CTLA-4 (P<0.05). The patients with high-risk scores demonstrated a worse prognosis than those with low-risk scores in the multiple datasets (GSE39582: P=0.0023; GSE17536: P=0.0008; immunotherapeutic cohort without platinum treatment: P=0.0014; immunotherapeutic cohort with platinum treatment: P=0.0027). Conclusion: We developed a robust immune-related prognostic signature with great performances in multiple cohorts and explored the characteristics of tumor immune microenvironment of colon cancer patients, which may give suggestions for the prognosis and immunotherapy in the future.